Pengaruh Layanan Pendidik terhadap Kepuasan Orang Tua siswa di TK Babussalam Sagulung - Yuni Resiyati; Supatmi Supatmi; Wasiah Wasiah (LPPI Yayasan Almahmudi bin Dahlan, 2023)
One of the efforts to improve the quality of a nation is to improve the quality of education. The quality of education services from the institution greatly affects customer satisfaction, PAUD services at Babussalam Sagulung Kindergarten have not run optimally. Many factors influence, namely internal factors, namely from the institution itself and external factors, namely factors from outside the school (parents and society). This research is a quantitative approach with a descriptive method that describes the effect of educational services of PAUD institutions on the satisfaction of parents of students at Babussalam Sagulung Kindergarten. In the aspect of parental satisfaction with educators, the highest accumulated score and the lowest score were 3.48 and 3.32, in the aspect of parental satisfaction with facilities and infrastructure. Based on the accumulation of the highest score (rating) 3.26 and the lowest is 2.56, in the aspect of parental satisfaction with management and financing based on the accumulation of the highest score (rating) obtained on the aspect of clarity of information or administrative services and the lowest is obtained on the aspect of how the school involves parents in school programs. To maximize the way the school involves parents in school programs, the school should be more open and intense meetings or meetings need to be held so that parents feel directly involved in program activities carried out by the school. Keywords: Service, Educator, Satisfaction